Efektifitas Senam Hamil terhadap Kejadian Rupture Perineum pada Ibu Bersalin di Puskesmas Limboto - Claudia, Juli Gladis; Adam, Wirdawaty S (Universitas Gorontalo, 2018)
Exercise in pregnancy have positive effect on the pregnancy outcomebecause stumulate to strengthen and maintain elasticity in abdominalmuscles and pelvic muscles which was associated with labor that whenstraining the muscles will relax actively that the head baby will outeasily and the pelvic floor muscle is weak, will not easily tear when willgive birth. The incidence of perineum rupture at Limboto CommunityHealth Center is 46,7%. The purpose of this study was to analyze theeffectiveness of gymnastics pregnancy against rupture perineum inMaternity at Limboto Community Health Center. The method of researchwas used pre-experimental research with statistical group comparisondesign with using chi square test. The population in this study were allthirty pregnant trimester III which amounted 30 people. The sample inthis study were 15 case groups and 15 control groups. The variablepregnant exercise was independent variabel and the dependentvariable was incidence of perineal rupture. The result of this researchby using chi square statistic test was showed t arithmetic 8,571, thatmean the respondent who have high pregnancy exercise did notexperience rupture perineum. Results p - value 0.009 with degree ofsignificance 0.05 (p < 0.05). The conclusion there was a significant effectof pregnancy exercise effectiveness on the incidence of perineal rupturein maternal mothers at Limboto Community Health Center.